Effect of fluoride varnish with added casein phosphopeptide-amorphous calcium phosphate on bond strength to enamel. Issue 6 (19th March 2017) - Bayrak, Sule; Tuloglu, Nuray; Ozer, Fusun; Blatz, Markus B.
Abstract: To investigate the effect of fluoride varnish with added casein phosphopeptide-amorphous calcium phosphate on the shear bond strength (SBS) of two adhesive systems to enamel. Specimens obtained from permanent teeth were randomly distributed among four groups for enamel pretreatment [Control (no treatment, CNT), Duraphat varnish (DV), Clinpro White varnish (CWV), MI Varnish (MIV)], and each group was further divided into two subgroups according to adhesive [Etch&rinse (Adper Single Bond, ASB), self-etch (Clearfil SE Bond, CSE)]. Specimens were stored in distilled water at 37 °C for 24 h. Cylindrical composite specimens (2.3 mm in diameter, 3.0 mm in height) were then bonded to the enamel surfaces. SBS tests were performed and data were analyzed with two-way ANOVA and Tukey's tests. For both CSE and ASB, SBS values of the CNT groups were significantly higher than those of all the enamel pretreatment groups ( p < 0.05). Among the enamel pretreatment groups, SBS values with both adhesive systems were lowest in the MIV groups, followed by CWV and DV groups. In conclusion, pretreatment of enamel surfaces with fluoride-containing varnishes reduced bonding performance of adhesive systems to enamel. MIV appeared to cause greater enamel surface alterations and precipitation, which interfered with adhesive bonding mechanisms.